2020
DOI: 10.3389/fnut.2020.584543
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Fasting and Caloric Restriction to Mitigate Radiation Damage—A Systematic Review

Abstract: Detrimental health effects from ionizing radiation to living organisms is one of the key concerns identified and addressed by Radiation Protection institutions, nationally and internationally on Earth and for human spaceflight. Thus, new methods for mitigating the adverse effects of ionizing radiation are urgently needed for terrestrial health and deep space exploration. Caloric restriction and (intermittent-) fasting have been reported to elicit a variety of immediate and long-term physiological effects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Data regarding IF and radiation are limited. 192 A preclinical study in a mouse model of pancreatic cancer examined fasting for 24 hours before abdominal radiation. 193 Fasting reduced toxicity, allowing for increasing doses of radiation, but it did not impair tumor cell death from radiation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Data regarding IF and radiation are limited. 192 A preclinical study in a mouse model of pancreatic cancer examined fasting for 24 hours before abdominal radiation. 193 Fasting reduced toxicity, allowing for increasing doses of radiation, but it did not impair tumor cell death from radiation.…”
Section: Future Directionsmentioning
confidence: 99%
“…In all quantitative reviews, a full metaanalysis was not possible as the outcomes were highly heterogeneous across studies and there was poor reporting of space medicine studies. However, all quantitative studies were able to perform effect size analysis and only two 10,27 had to rely on significance result reporting. One review 13 used qualitative methods to present a thematic analysis of technical documents from grey literature sources required to answer the technical nature of the research question.…”
Section: Resultsmentioning
confidence: 99%
“…However, based on the initial review questions tackled, it is apparent that controlled trials, repeated studies and use of standardized outcome measures across studies often do not exist or have been poorly reported, making Cochrane based meta-analyses not possible for some research questions. Therefore, alternate acceptable analyses were performed in a hierarchy of effect size analysis, qualitative analyses 20,26 (individually or combined with quantitative analysis within an integrated approach) 9 and finally, if no other method is possible and there is a justified reason for continuing, reporting of significance testing results from included papers 27 . In extreme cases if no published data exists on a key topic, an empty review could be published to provide comprehensive gap analysis and used to stimulate primary research.…”
Section: Deciding Main Synthesis Methodsmentioning
confidence: 99%
“…Our findings suggested that DR could activate mechanisms consequently resulting in suppression of radiation-induced genotoxicity and GI. Since the early work by Moreschi and McCay et al [59,60], the rapidly growing body of evidence on the effects from dietary intervention has shown that diet intervention has a great impact on health, pointing to a multitude of benefits affecting numerous physiological systems [61]. Diet intervention also elicits a variety of immediate and long-term physiological effects, in particular, beneficial effects on numerous diseases including cancer in experimental models [22].…”
Section: Discussionmentioning
confidence: 99%